An innovative approach to evaluating organisational change. (24th February 2005) - Henderson, Joan; McAdam, Rodney; Parkinson, Steven
This paper addresses the difficult problem of how to improve the process of evaluating organisational change. Given that the data emergent from an evaluative exercise will strongly influence the subsequent strategic and operational decisions taken by organisational managers, it is critical that the evaluation approach itself is capable of delivering high quality, accurate and timely data. The aim of this paper is to examine the role of the IT-based Optionfinder Technology used in conjunction with focus groups, in generating management decision-making data, and reflecting the changes in key performance indicators in a utility organisation. The case study research evaluates the innovative integrative approach adopted by the utility organisation and concludes that the proposed approach contributes to improvements in the decision-making capability of managers.